2012
DOI: 10.1002/elsc.201100087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the hydrodynamic environment and oxygen mass transfer on plant cell growth and milk‐clotting protease production in a stirred‐tank reactor

Abstract: Industrial‐scale plant cell based bioprocesses are limited because of technological challenges associated with mass transfer and mixing in the heterogeneous broth, which typically displays non‐Newtonian characteristics. Cultures of Centaurea calcitrapa cells, presenting milk‐clotting activity, were established in a 7‐L stirred‐tank reactor (STR), keeping the initial mass transfer conditions constant, to gain a better understanding of the effects of the hydrodynamic environment and mass transfer on protease pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Selection of the proper process parameters (for example power consumption or gas hold-up) which characterise the mixing operation in the agitated vessel allows to ensure appropriate conditions for conducting chemical and biochemical processes (Garcia-Ochoa and Gomez, 2009;Martin et al 2008a,b;Montante et al, 2007Montante et al, , 2008Raposo and Lima-Costa, 2012;Scargiali et al, 2007;Van't Riet, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Selection of the proper process parameters (for example power consumption or gas hold-up) which characterise the mixing operation in the agitated vessel allows to ensure appropriate conditions for conducting chemical and biochemical processes (Garcia-Ochoa and Gomez, 2009;Martin et al 2008a,b;Montante et al, 2007Montante et al, , 2008Raposo and Lima-Costa, 2012;Scargiali et al, 2007;Van't Riet, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Raposo et al [53] showed that this type of sparger is more efficient with high K L a values than those obtained with the L-shaped sparger. The porous sparger promotes the formation of microbubbles with a high retention time in the liquid phase, thus enabling a greater mass transfer of oxygen and consequently a greater accessibility of this gas to the cells.…”
Section: Effect Of Oxygen Availability In Lipid Accumulation (High Aementioning
confidence: 88%
“…Impeller tip speed ( ν i ) expressed in m/s was calculated according to Equation described by Raposo and LimaCosta : νi=π×N×Di,where N is the rotational speed of the impeller (1/s) and Di is the impeller diameter (0.05 m). The average energy dissipation rate ( ε ), expressed in kW/kg is the specific power input (kW/m 3 ) ( P / V ) divided by the density of the culture, that is, ρ (1.018 kg/m 3 ), according to Equation : ε=P/ρV=NpN3Di5/V,where N is the rotational speed of the impeller (1/s), Di is the impeller diameter (0.05 m), Np is the power number for the relevant impeller at the prevailing value of the Reynolds number ([ ND i 2 p ] /μ app ), and v is the dissipation of medium volume.…”
Section: Methodsmentioning
confidence: 99%